Association between mortality and cognitive change over 7 years in a large representative sample of UK residents. - Shipley BA; Der G; Taylor MD; Deary IJ; Shipley, Beverly A; Der, Geoff; Taylor, Michelle D; Deary, Ian J (Psychosomatic Medicine, 2007)
Objective: To examine the association between change in reaction time and cognitive performance over 7 years and the risk of death from all causes and some specific causes after controlling for known risk factors.Methods: The sample comprised members of the Health and Lifestyle Survey (HALS) of community-dwelling adults in England, Scotland, and Wales. Baseline testing (HALS1), involving 9003 people, took place in 1985 and 1986. Sociodemographic, lifestyle, health, and physiological information was collected. Cognitive functioning was measured using tests of simple and choice reaction time, a short memory test, and a test of visual-spatial reasoning. Follow-up testing (HALS2) took place in 1991 and 1992, when 5352 members of the study were administered the same questionnaires, physiological examinations, and cognitive tests. The sample has been followed for mortality up to June 2005.Results: After controlling for age, gender, and the relevant baseline cognitive test scores, greater declines between HALS1 and HALS2 on simple reaction time mean and variability, choice reaction time mean and variability, memory and visual-spatial reasoning were associated with significantly increased risks of death from all causes, all cardiovascular diseases (CVDs), coronary heart disease (CHD), stroke, and respiratory disease. These associations were only slightly attenuated after adjusting for occupational social class, educational, smoking, alcohol consumption, physical activity, body mass index, blood pressure, and lung function.Conclusions: Decline in performance of reaction times and simple cognitive tasks across a 7-year period was associated with an increased risk of death from all causes, all CVDs, CHD, stroke, and respiratory disease up to 13 years later, even after adjustment for known risk factors.